تركيز اليورانيوم لبعض مناطق تربة مدينة بغداد - العراق - كاظم, نضال حسن; قاسم, رياض يونس; علوان, عدوية محسن (Al-Nahrain Journal of Science, 2012)
The research aims to measure the concentrations of uranium for (20) soil samples covering (4) areas in Baghdad with different depths (10–20–30–40–50) cm, The concentrations were estimated by using the technique of counting the fission fragments in (CR-39) detector resulting from the fission of nuclei 235U by the thermal neutrons from the neutronic source (241Am-Be) with a neutronic flux of (5×103 n. cm2.s1). The concentrations of uranium were determined by the given calculations which were compared with the standard samples after the calibration curve which was represented by the relation between the concentrations of the uranium nuclei fission traces with the known standard concentrations of uranium in the standard samples. The relation was linear as in the diagram (1). From the diagram slope, the average concentrations of uranium in the soils were as follows:Al-Waziriyah 0.397 ± 0.09 ppm, Al-Za'faraniyah 0.47 ± 0.06 ppm, Al-Durra 0.402 ± 0.09 ppm, Al-Rashdiyah 0.291 ± 0.09 ppm.